2012
DOI: 10.1007/s10792-012-9522-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of central corneal thickness to postural IOP changes in patients with and without glaucoma in southern India

Abstract: To evaluate the relationship of central corneal thickness to the changes in intraocular pressure (IOP) in the sitting and supine position. Observational case-control study. The study group included Primary open-angle and chronic angle closure glaucoma patients. The control group consisted of patients without glaucoma seen for their routine eye examination. Central corneal thickness was measured by ultrasound pachymetry. Patients were then randomized to IOP measurement by Tonopen either sitting or supine after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the other study, Singleton et al [11] compared postural changes in IOP in only 11 normal subjects, relative to several groups of patients who had different types of autonomic dysfunction; they concluded that no statistically significant postural changes in IOP occurred in normal subjects. Additionally, multiple authors reported measuring IOP in sitting and supine positions using different devices, such as the ICP [16], TonoPen [17,18,19,20,21], and AVIA [13]. Some others compared different tonometers [13,22], but we found no reports of IOP measurements in subjects in the ST position.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the other study, Singleton et al [11] compared postural changes in IOP in only 11 normal subjects, relative to several groups of patients who had different types of autonomic dysfunction; they concluded that no statistically significant postural changes in IOP occurred in normal subjects. Additionally, multiple authors reported measuring IOP in sitting and supine positions using different devices, such as the ICP [16], TonoPen [17,18,19,20,21], and AVIA [13]. Some others compared different tonometers [13,22], but we found no reports of IOP measurements in subjects in the ST position.…”
Section: Discussionmentioning
confidence: 64%
“…In another study, IOP was measured in 19 healthy young Korean subjects in the sitting and supine positions, revealing an increase of approximately 3 mmHg from the first to the second position [19]. In another investigation, the same device was used to measure IOP in both sitting and supine positions in 45 glaucoma patients and 46 healthy subjects; both groups showed a statistically significant increase in mean IOP from the sitting position to supine position, which was higher in glaucomatous patients (2.3 mmHg) than in healthy subjects (1.2 mmHg) [21].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, the increase in IOP between sitting and supine position was reported as 1.8 mmHg using Perkins applanation tonometer, 2.5-3.9 mmHg with pneumotonometer, 1.2 mmHg with Tono-Pen, and 4.1 mmHg with Goldman applanation tonometry. 1,26,27,28,29 Mosaed et al 30 reported relatively small postural change in IOP in healthy young adults and elderly individuals with healthy eyes, while another study reported that postural IOP changes in these two populations were nonsignificant. 31…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Thus, parameters including cup-to-disc ratio, retinal nerve fiber layer, and visual field assessment should be used in patients with MC with raised IOP. 19…”
Section: Discussionmentioning
confidence: 99%